Perfil e atuação dos feirantes sobre produtos orgânicos no RN - Araújo, Yara Patrícia Ginane de (Universidade Federal Rural do Semi-Árido, 2020)
The growth in demand for healthy food, over the years, is greater than the population that suffers from disease prevention and life improvement, influences the increase in consumption of organic products, it is not what consumers prefer to use these products at fairs. With this, this article had as main objective to evaluate the perception of the weirdos in some cities of the state of Rio Grande do Norte, in relation to the commercialization and knowledge about organic products, as well as to identify the profile of the weirdos. To this end, this article is a descriptive case study, of an applied nature with a combined and used approach or as a data collection technique. A research was carried out in five stages: literature review, choice of cities, data collection, data analysis and recommendations for improvements. When 90 marketers were interviewed and the results demonstrated with the same items above 40 years old, low education and with a little more than half with the female gender, they are predominant for the purchase of products and purchase of products with little knowledge about organic production.
Monografia
Keywords: Alimentos saudáveis; Cultivo orgânico; Feiras livres; Healthy foods; Organic cultivation; Free fairs; ENGENHARIAS::ENGENHARIA DE PRODUCAO